Minutes of 17th technical and progress monitoring (TPM) meeting of BRACU new campus (session I) - Brac University (Brac University, 2023)
Minutes of the 17th Technical and Progress Monitoring (TPM) meeting (session l) of BRACU new campus, held on 17th June, 2019.